2022
DOI: 10.3758/s13415-022-00996-z
|View full text |Cite
|
Sign up to set email alerts
|

Pupil dilation and response slowing distinguish deliberate explorative choices in the probabilistic learning task

Abstract: This study examined whether pupil size and response time would distinguish directed exploration from random exploration and exploitation. Eighty-nine participants performed the two-choice probabilistic learning task while their pupil size and response time were continuously recorded. Using LMM analysis, we estimated differences in the pupil size and response time between the advantageous and disadvantageous choices as a function of learning success, i.e., whether or not a participant has learned the probabilis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 76 publications
9
23
0
Order By: Relevance
“…Secondly, in addition to the overall heightened dilation of pupils in PC phase, we found that only in this phase value-driven modulation of pupil size was significant, and this effect was predictive of the behavioral speed modulation. Modulation of pupil responses by reward value is 10.3389/fnhum.2022.1062168 in line with a number of previous findings Braver, 2013, 2014;Massar et al, 2016;Koelewijn et al, 2018;Pietrock et al, 2019;Walsh et al, 2019) and indicates that when the delivery of reward is contingent on task performance, higher reward incentives could efficiently mobilize the processing resources, and settle an efficient relationship between the speed and accuracy of choices, effects that are also reflected in the taskevoked pupil dilatation and have been reported across motor (Naber and Murphy, 2020), perceptual (Walsh et al, 2019), and cognitive (Kozunova et al, 2022) tasks. On the other hand, the lack of value-driven modulation of pupil responses for PR cues is in line with effects reported in previous studies, where reward-driven modulations of pupil size were only found during the learning of reward associations (Anderson and Yantis, 2012) but were absent during the test phase when rewardassociations were implicit (Hammerschmidt et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Secondly, in addition to the overall heightened dilation of pupils in PC phase, we found that only in this phase value-driven modulation of pupil size was significant, and this effect was predictive of the behavioral speed modulation. Modulation of pupil responses by reward value is 10.3389/fnhum.2022.1062168 in line with a number of previous findings Braver, 2013, 2014;Massar et al, 2016;Koelewijn et al, 2018;Pietrock et al, 2019;Walsh et al, 2019) and indicates that when the delivery of reward is contingent on task performance, higher reward incentives could efficiently mobilize the processing resources, and settle an efficient relationship between the speed and accuracy of choices, effects that are also reflected in the taskevoked pupil dilatation and have been reported across motor (Naber and Murphy, 2020), perceptual (Walsh et al, 2019), and cognitive (Kozunova et al, 2022) tasks. On the other hand, the lack of value-driven modulation of pupil responses for PR cues is in line with effects reported in previous studies, where reward-driven modulations of pupil size were only found during the learning of reward associations (Anderson and Yantis, 2012) but were absent during the test phase when rewardassociations were implicit (Hammerschmidt et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…The hypothesized relationship between NE and random exploration is in line with previous work showing that pupil size -as an indirect measure of NE level (4,13) -correlates with variability in the evidence accumulation process (38,39), magnitude of noise in perceptual tasks (40), and choice randomness in value-based decision making (9,(41)(42)(43)(44). These pupillometry studies suggest that pupil size could represent the computation of total uncertainty during reinforcement learning, though this has not been directly tested yet.…”
supporting
confidence: 81%
“…This conflict arises between at least two simultaneously active competing internal models, or 'task sets' (Domenech et al, 2020;Koechlin, 2020) one being a predominant response tendency (exploitation), and the otherits conscious alternative (exploration). Our recent pupillometric study lends support to this assumption (Kozunova et al, 2022): we found that such explorative choices compared to exploitative ones are accompanied by larger pupil dilation and longer decision time. We speculated that this state of conflict supposedly entails an increase in the degree of processing required to make the deliberately explorative decisions.…”
Section: Introductionsupporting
confidence: 66%
“…A recent pupillometric study (Kozunova et al, 2022) revealed that advantageous choices that immediately preceded and immediately followed explorative choices significantly differed from the advantageous choices committed within the periods of continuous exploitation. This finding hints that the internal state related to exploration modulates brain activity on a scale longer than duration of one trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation